Perkembangan Tarekat Naqsyabandiyah di Kecamatan Akabiluru Kabupaten Lima Puluh Kota (1964-2010) - Sari, Indah Permata (Pendidikan Sejarah, 2014)
This thesis examine the development of the: Development Tarekat Naqsyabandiyah IN Subdistrict Akabiluru sub Lima puluh kota (1964-2010).the research done because the tarekat recognized as based on the Quran and Hadisth, seen since the early entry to the learn tarekat Naqsyabandiyah have growth, because the teachings of the tarekat was able to give change to people and forms the basis of the teachings and ways of implementing the activities of this tarekat invite Naqsyabandiyah seclusion and tarekat who do dzikir, the tarekat teachings brought by the Sufis and scholars who study religion in Mecca. At the beginning of the growing tarekat Naqsyabandiyah in flagstones on the Sheikh Damrah not get a lot of followers. In 1964 Sheikh Damrah new pupils have 5 people, because people do not quite understand, and agree to Naqsyabandiyah tarekat. At the beginning of the growing tarekat Naqsyabandiyah originated from years 1964-2010 only a small group that follows the teachings of the tarekat Naqsyabandiyah. In 1964 before the H. Syarani Chalil being a leader is Sheikh Damrah Naqsyabandiyah tarekat, after which in 1992 was replaced by a new Syarani H. Chalil also earned Datuak Oyah parentage or lineage. H. Syarani Chalil title when appointed as leader of the Order Naqsyabandiyah in 1992 at the time the members of as many as 72 people and in 2010 during the leadership of H. Syarani Chalil members has reached 155 people. Based on the results of the study showed that this Naqsyabandiyah tarekat has developed a pattern of teaching by providing seclusion and remembrance that have several levels, because it is able to teach the public to learn more about Islam. Teaching of the order sought to draw closer to God. Through mysticism and dzikir. Where mysticism was an activity Dzikir Allah, tarekat followers put dzikir for the first than interest the World.